2011
DOI: 10.1124/dmd.111.040980
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Metabolism of a Selective δ-Opioid Receptor

Abstract: ABSTRACT:4-({4-[(2-Hydroxy-ethyl)-methyl-carbamoyl]-phenyl}-quinolin-8-ylmethylene)-1-thiazol-4-ylmethyl-piperidinium (compound I) is a selective agonist of ␦-opioid receptor developed for the treatment of depressive and anxiety disorders. The in vitro biotransformation studies using rat, dog, and human hepatocytes showed that the metabolites detected in human hepatocytes were also found in either rat or dog hepatocytes. M1 (N-dealkylation), M2 (Ndemethylation), and M4 (carboxylic acid metabolite) were major p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Thevis et al [32], who accomplished an MA of lower than 3 ppm for the period of analysis, observed ppm errors between −2.0 and −0.2 for the protonated molecules and between −1.2 and 4.7 ppm for the product ions after HCD without any lock masses. Similar data were published by Guo et al [24] showing ppm errors between 1.4 and 3.1 ppm using a resolution of 15,000 on an LTQ-OT studying the metabolism of a selective delta-opioid receptor agonist. The additional use of lock masses can enhance MA.…”
Section: Resolution and Mass Accuracysupporting
confidence: 86%
See 3 more Smart Citations
“…Thevis et al [32], who accomplished an MA of lower than 3 ppm for the period of analysis, observed ppm errors between −2.0 and −0.2 for the protonated molecules and between −1.2 and 4.7 ppm for the product ions after HCD without any lock masses. Similar data were published by Guo et al [24] showing ppm errors between 1.4 and 3.1 ppm using a resolution of 15,000 on an LTQ-OT studying the metabolism of a selective delta-opioid receptor agonist. The additional use of lock masses can enhance MA.…”
Section: Resolution and Mass Accuracysupporting
confidence: 86%
“…The first group uses mainly IT-based mass spectrometers such as OT-or TOF-based detectors for metabolite and structure elucidation. Guo et al [24] used an IT-OT for the identification of metabolites of the selective δ-opioid receptor agonist 4-([4-[(2-hydroxyethyl)methylcarbamoyl]phenyl] quinolin-8-yl-methylene)-1-thiazol-4-yl-methylpiperidinium in hepatocyte samples. Liu et al [18] used LC coupled with IT-TOF for studying the metabolism of olaquindox in rat liver microsomes and structural elucidation of metabolites.…”
Section: Analytical Strategies In Drug Metabolism Studies Using Hrmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasma samples were prepared by centrifugation of blood samples at 3000 ×g for 10 min. Plasma samples were pooled in a time proportional manner to obtain a 0 to 4 h representative pooled sample for each rat [23]. An aliquot of 0.3 mL of pooled plasma sample was mixed vigorously with 1 mL of acetonitrile-methanol (v/v, 2 : 1) and then centrifuged at 10,000 ×g for 10 min to remove protein.…”
Section: Methodsmentioning
confidence: 99%